PENERAPAN MODEL PEMBELAJARAN THINK-TALK-WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Rahmad Hidayat; Tri Astari (Bajang Institute, 2021)
The root of the research problem is that students' perceptions of mathematics tend to be negative, students' interest in learning is less because they can make money, teachers lack knowledge about learning models, so that the learning process tends to be monotonous, and student learning outcomes in mathematics are low. The type of research is Classroom Action Research (CAR), carried out in Class V UPT SPF SDN 105336 Rantau Panjang. Student learning outcomes before using the Think-Talk-Write (TTW) learning model: there were 21 students who scored in the incomplete category with an average value of 20.95. Furthermore, after using the Think-Talk-Write (TTW) learning model in the first cycle, the average student learning outcomes increased by 3 students (14.28%) in the complete category and 18 students (85.71%) in the incomplete category. In the first cycle it is considered not optimal because there are still many students who have not achieved the complete score and students look less active in learning. After making improvements, in the second cycle, student learning outcomes have increased. In the second cycle test results obtained an average of 80.95 with as many as 19 students (90.48%) in the complete category and 2 students (9.52%) in the incomplete category. The results of the observation are that the percentage of the success rate of teacher performance is 95.8%, the criteria are very good and student learning activities reach 75.9%, the criteria are sufficient. This shows that there is an increase in students' mathematics learning outcomes with the application of the Think-Talk-Write (TTW) learning model.